Crucial residue involved in L-lactate recognition by human monocarboxylate transporter 4 (hMCT4). - Shotaro Sasaki (PLoS ONE, 2013)
BACKGROUND: Monocarboxylate transporters (MCTs) transport monocarboxylates such as lactate, pyruvate and ketone bodies. These transporters are very attractive therapeutic targets in cancer. Elucidations of the functions and structures of MCTs is necessary for the development of effective medicine which targeting these proteins. However, in comparison with MCT1, there is little information on location of the function moiety of MCT4 and which constituent amino acids govern the transport function of MCT4. The aim of the present work was to determine the molecular mechanism of L-lactate transport via hMCT4. EXPERIMENTAL APPROACH: Transport of L-lactate via hMCT4 was determined by using hMCT4 cRNA-injected Xenopus laevis oocytes. hMCT4 mediated L-lactate uptake in oocytes was measured in the absence and presence of chemical modification agents and 4,4'-diisothiocyanostilbene-2,2'-disulphonate (DIDS). In addition, L-lactate uptake was measured by hMCT4 arginine mutants. Immunohistochemistry studies revealed the localization of hMCT4. RESULTS: In hMCT4-expressing oocytes, treatment with phenylglyoxal (PGO), a compound specific for arginine residues, completely abolished the transport activity of hMCT4, although this abolishment was prevented by the presence of L-lactate. On the other hand, chemical modifications except for PGO treatment had no effect on the transport activity of hMCT4. The transporter has six conserved arginine residues, two in the transmembrane-spanning domains (TMDs) and four in the intracellular loops. In hMCT4-R278 mutants, the uptake of L-lactate is void of any transport activity without the alteration of hMCT4 localization. CONCLUSIONS: Our results suggest that Arg-278 in TMD8 is a critical residue involved in substrate, L-lactate recognition by hMCT4.